1996
DOI: 10.1203/00006450-199602000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Brain Injury after Perinatal Hypoxia-Ischemia Is Exacerbated in Copper/Zinc Superoxide Dismutase Transgenic Mice

Abstract: The role of superoxide radical formation in the pathogenesis of perinatal hypoxic-ischemic injury was examined using transgenic (Tg) mice expressing three times normal amounts of copper/zinc-superoxide dismutase (CuZn/SOD). Fourteen litters of postnatal d 7 strain 218/3 mice were subjected to right common carotid artery ligation followed by 90 min of hypoxia in an 8% oxygen/humidified chamber maintained at 37 degrees C. Both Tg mice (n = 32) and their nontransgenic (nTg) littermates (n = 30) survived the injur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
121
1

Year Published

1997
1997
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 180 publications
(129 citation statements)
references
References 24 publications
7
121
1
Order By: Relevance
“…Neuroprotection by Blocking Injury Progression after P8 in the HI-Injured Ipsilateral Forebrain, Hippocampus, and Thalamus Unilateral carotid artery ligation followed by 45 minutes of hypoxia produces a moderate-to-severe brain injury in immature mice (Ditelberg et al, 1996;Graham et al, 2004) as shown in this study in vehicle-treated mice ( Figure 1A). This injury is attenuated by necrostatin when administered immediately after HI ( Figure 1A).…”
Section: Necrostatin Provides Delayed and Persistentsupporting
confidence: 59%
See 1 more Smart Citation
“…Neuroprotection by Blocking Injury Progression after P8 in the HI-Injured Ipsilateral Forebrain, Hippocampus, and Thalamus Unilateral carotid artery ligation followed by 45 minutes of hypoxia produces a moderate-to-severe brain injury in immature mice (Ditelberg et al, 1996;Graham et al, 2004) as shown in this study in vehicle-treated mice ( Figure 1A). This injury is attenuated by necrostatin when administered immediately after HI ( Figure 1A).…”
Section: Necrostatin Provides Delayed and Persistentsupporting
confidence: 59%
“…Postnatal day (P)7 mice were exposed to HI as described previously using the Vannucci model as adapted for neonatal mice (permanent ligation of the right common carotid and FiO 2 = 0.08 minutes  45 minutes) (Ditelberg et al, 1996;Graham et al, 2004). Fifteen minutes after the hypoxic exposure, the pups were briefly reanesthetized with isofluorane and 0.1 mL of 80mmol necrostatin, Nec-1, 5-(1H-Indol-3-ylmethyl)-(2-thio-3-methyl) hydantoin (Alexis Biochemical, Plymouth Meeting, PA, USA) or vehicle, methyl-b-cyclodextrin (Sigma, St Louis, MO, USA) was injected intracerebroventricularly.…”
Section: Hypoxic-ischemic Injury and Drug Administrationmentioning
confidence: 99%
“…These findings, however, are in contrast to those observed after injury to the immature rodent brain (Ferriero, 2001). SOD1 overexpression in the neonatal rodent exacerbates hypoxic-ischemic brain injury (Ditelberg et al, 1996;Fullerton et al, 1998). This pronounced vulnerability is likely because of the imbalanced overproduction of H 2 O 2 from O 2 KÀ , and a lack of compensatory protective mechanisms (Fullerton et al, 1998).…”
Section: Vulnerability Of the Developing Brain To Injurymentioning
confidence: 83%
“…It is well known from previous studies that the mechanisms underlying postischemic brain damage 1,2,5,19 as well as the role of adenosine receptors 3 differ in many ways between young and old mice (see below). An age-dependent difference in A2AR is also indicated by the fact that in adult rats an A2AR antagonist has a clear cerebroprotective effect, 13 consistent with the findings in adult A2AR…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies show that there are important differences between animals of different ages. [1][2][3][4][5] It is therefore important to study mechanisms in models of ischemia in the immature brain.…”
mentioning
confidence: 99%